Molecular detection of waterborne pathogens in infants' drinking water and their relationship with water quality determinants in eastern Ethiopia: loop-mediated isothermal amplification (LAMP)-based study - Samuel Mebrahtom Gebregziabher; Alemayehu Worku Yalew; Heven Sime; Adugna Abera (IWA Publishing, 2024)
Cryptosporidium, Shigella, toxin-producing Escherichia coli, and rotavirus were reported to be the most responsible for severe and fatal diarrhea among infants. This study aimed to investigate the presence of these pathogens in infants' drinking water samples and analyzing using water quality determinants in eastern Ethiopia. A molecular (LAMP)-based cross-sectional study design was employed. A total of 410 and 37 water samples were tested from infant point-of-use at household and corresponding water source, respectively, from June 2020 to May, 2021. Cryptosporidium, Shigella, toxin-producing E. coli, and rotavirus were detected in 28.5, 30.0, 26.3, and 32.2%, of water samples tested from infant point-of-use, respectively. About 13.2% of the water samples were positive for all (four) pathogens together. Cryptosporidium, Shigella, toxin-producing E. coli, and rotavirus were detected in 27.0, 32.4, 29.7, and 37.8%, of water samples tested from water sources, respectively. Positive significant correlation was observed between infant point-of-consumption and water sources from which it is drawn toward the presence of each targeted pathogen. Unimproved water source showed a strong significant association with the presence of Cryptosporidium, Shigella and toxin-producing E. coli. Therefore, efforts should be made in development of improved water sources, source protection safety and health education to caretakers of infants. HIGHLIGHTS Highest prevalent agent detected in water samples was rotavirus (32.2%), followed by Shigella (30.0%), Cryptosporadium (28.5%), and toxin-producing E. coli (26.5%).; Positive correlation was observed between drinking water at point-of-use and water sources on presence of pathogens.; Significant association was observed between unimproved water source and presence of Cryptosporidium, Shigella, and toxin-producing E. coli.;